2014
DOI: 10.3892/ol.2014.1906
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RECK and MMP-2 in salivary adenoid cystic carcinoma: Correlation with tumor progression and patient prognosis

Abstract: Reversion-inducing cysteine-rich protein with Kazal motifs (RECK), a glycosylphosphatidylinositol-anchored glycoprotein, inhibits the enzymatic activities of certain matrix metalloproteinases (MMPs). RECK has been studied in numerous human tumors, but the expression of RECK in salivary adenoid cystic carcinoma (SACC), and its correlation with patient prognosis, has never been investigated thus far. In the present study, the expression of RECK and MMP-2 was evaluated in two ACC cell lines and in 83 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…In a previous study, the RECK expression level was inversely correlated with the MMP9 expression level in nasopharyngeal carcinoma (27). Furthermore, there was a significant association between the positive expression of RECK and that of MMP2 in adenoid cystic carcinoma (28). These findings suggest that RECK has an important role in regulating the proliferation and migration of normal epithelial cells and carcinoma cells (29).…”
Section: Discussionmentioning
confidence: 52%
“…In a previous study, the RECK expression level was inversely correlated with the MMP9 expression level in nasopharyngeal carcinoma (27). Furthermore, there was a significant association between the positive expression of RECK and that of MMP2 in adenoid cystic carcinoma (28). These findings suggest that RECK has an important role in regulating the proliferation and migration of normal epithelial cells and carcinoma cells (29).…”
Section: Discussionmentioning
confidence: 52%
“…RECK is a newly discovered tumor-suppressor gene. RECK protein has a unique inhibitory effect on the expression and activity of MMPs, as a matrix metalloproteinase inhibitor, and RECK gene expression is closely related to tumor invasion, metastasis and angiogenesis (12). Studies have shown that RECK gene expression in liver (13), pancreatic (14), breast (15) and lung cancer (16) is negatively correlated with tumor invasiveness, and patients with high RECK gene expression have a significantly more favorable prognosis than those with low expression.…”
Section: Introductionmentioning
confidence: 99%
“…All ECM components can be degraded by MMPs and each element is cleaved by a specific member of the MMP family. The MMP family plays a critical role in the process of tumor cell invasion P-value Total score P-value Intensity P-value Percentage of positive cells [28][29][30]. The MMP activity is regulated at different levels, such as cellular receptors, presence of inhibitors, compartmentalization and gene expression.…”
Section: Discussionmentioning
confidence: 99%